A historical sketch of cultural anthropology in Japan: associations, museums, research projects and textbooks - Hirochika NAKAMAKI (International Journal of Anthropology and Ethnology, 2022)
Abstract The aim of my presentation is to introduce a brief history of anthropological studies in Japan, particularly focusing on the associations, museums, research projects and textbooks. As for associations, I will describe about the Anthropological Society of Nippon (founded in 1884), the Japanese Society of Ethnology (founded in 1934) and its renamed association, the Japanese Society of Cultural Anthropology (since 2004). JASCA has approximately 2000 members. Regarding museums, I will pick up mainly National Museum of Ethnology (Minpaku, founded in 1974), as well as Little World Museum of Man (founded in 1983) and National Ainu Museum (Upopoy, founded in 2020). With regard to research projects, special research projects and inter-university research projects of Minpaku and panels of JASCA conferences are major targets of analysis. Lastly, I can cite at least 50 textbooks for students and several encyclopedias on anthropology. I will also show the variety of anthropological publications and popular topics in the contemporary book market.